Utilizing Video versus Direct Laryngoscopy to Intubate Simulated Newborns while Contained within the Incubator: A Randomized Crossover Study - Ozawa, Yuri; Takahashi, Shigehiro; Miyahara, Humiko; Hosoi, Kenichiro; Miura, Mazumi; Morisaki, Naho; Ito, Yushi; Isayama, Tetsuya (American Journal of Perinatology, 2020)
Objective The use of video laryngoscopy for intubating neonates in ergonomically challenging settings has not been studied well. We aimed to assess the usefulness of video laryngoscopy for experienced neonatologists to intubate neonatal manikins in incubators via side hand ports or head window.Study Design In this randomized crossover trial at three neonatal intensive care units in Japan, 27 neonatologists were randomized into two groups, namely, those intubating neonatal simulators using video laryngoscopy and then using direct laryngoscopy, or vice versa. The intubations were performed via hand ports or head window without opening top and side walls in incubators in two manikin positions (rotated 90° or unrotated). Glottis visualization (0–100%), success rate, intubation time, and ease of laryngoscopy (from 1 [very difficult] to 10 [very easy]) were compared between video laryngoscopy and direct laryngoscopy. Generalized linear models were used for the analyses.Results This study assessed 108 intubations performed by 27 neonatologists. The use of video laryngoscopy improved the glottis visualization by 14% (95% confidence interval, 7.4–20%; p < 0.01) and easiness scores of laryngoscopy by 0.8 (0.2–1.4; p < 0.01), but did not reduce the intubation time.Conclusion Video laryngoscopy is useful for experienced neonatologists for intubating neonatal manikins in incubators without opening the top or side walls.
Keywords: video laryngoscopy; neonatal intensive care units; incubator; intubation